(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This study evaluated the effects of positive reinforcement with increased magnitude (earning points) and aversive control (losing points) on the rule-following behavior. Participated sixteen undergraduate students that were exposed to a matching-to-sample task. The participants, divided in two groups, should choose one of two comparison-stimuli in the presence of a contextual stimulus. The Gain Group started with zero points and produced three points for each correct response; the Loss Group started with 80 points and each incorrect response produced the loss of one point. A total of 80 trials, divided in four blocks, were presented. During the C1 and C2 blocks, contingencies corresponded to the rules; during D1 and D2 blocks, contingencies were discrepant to the rules. The Loss Group presented an average of correct responses significantly higher than the Gain Group during discrepant blocks. The increasement in the reinforcer magnitude did not present the same effects of aversive control on the abandonment of instruction-following, confirming previous studies.